Evaluasi KIPPas (Kartu Instrumen Prediktor Pangastuti) Jogja sebagai Instrumen Prediktor Disfungsi Dasar Panggul Pasca Persalinan Vaginal - Fauzan Achmad Maliki; Nuring Pangastuti; Rukmono Siswishanto (JURNAL KESEHATAN REPRODUKSI, 2022)
Background: Postpartum pelvic floor dysfunction is pelvic floor disorder, which can be in the form of pelvic organ prolapse, urinary problem, defecation problem or sexual dysfunction. The incidence of postpartum pelvic floor dysfunction occurs in 46% of postpartum women. Until now, there is no standard instrument used to estimate the incidence of postpartum pelvic floor dysfunction. In previous studies, an instrument was obtained, namely KIPPas Jogja, to estimate the incidence of pelvic floor dysfunction after delivery, but it was still not sufficient for the number of research samples needed.Objective: To evaluate the Pangastuti Jogja Predictor Instrument Card (KIPPas Jogja) as a predictor of pelvic floor dysfunction in the form of pelvic organ prolapse after vaginal delivery.Method: This study was a prospective cohort study. Subjects who gave vaginal delivery were examined according to the KIPPas Jogja instrument and then evaluated for the diagnosis of pelvic floor dysfunction in the form of pelvic organ prolapse with POPQ examination and complaints of pelvic floor dysfunction using the PFDI and FSFI instruments at 3 months postpartum.Results and Discussion: From 133 research subjects, the results of the KIPPas Jogja assessment are high risk in 42.9% of subjects and low risk in 57.1% of subjects. The incidence of pelvic floor dysfunction in the form of pelvic organ prolapse was found in 69.17% subjects. Complaints of pelvic floor dysfunction were present in 20.31% subjects and complaints of sexual dysfunction in 11.3% subjects. The sensitivity of KIPPas Jogja is 80% and specificity is 95% with a positive predictive value of 97% and a negative predictive value of 68% to detect pelvic dysfunction in the form of pelvic organ prolapse. Meanwhile, to predict complaints of pelvic floor dysfunction, measured with PFDI-20, the sensitivity was 93% and specificity was 52%, and the positive predictive value was 33% and the negative predictive value was 96%. To predict sexual dysfunction, KIPPas obtained sensitivity of 64%, specificity of 42% with a positive predictive value of 10% and a negative predictive value of 92%.Conclusion: KIPPas Jogja can be used as a predictor of postpartum pelvic floor dysfunction. Keywords: postpartum pelvic floor dysfunction, KIPPas Jogja, POPQ, PFDI-20, FSFI